Echocardiographic patterns in asphyxiated neonates - Maswin Masyhur; Idham Amir; Sukman Tulus Putra; Alan Roland Tumbelaka (Paediatrica Indonesiana, 2009)
Background Neonatal asphyxia is a disorder in neonates dueto decreased oxygenation (hypoxia) and decreased perfusion toorgans (ischemia). Duration of asphyxia and early managementinfluence the severity of organ dysfunction, including the heart.Objectives To obtain patterns of cardiac abnormality inneonatal asphyxia in Cipto Mangunkusumo Hospital withechocardiography. Design A cross-sectional study was performed on 22 asphyxiated neonates and 22 other non-asphyxiated neonates from March to October 2008. Inclusion criteria were term neonates, Apgar score :S 6 in the first minute for asphyxiated neonates and ?. 7 for normal/non-asphyxiated neonate. Echocardiographic examination was performed before the age of 48 hours.Results There were 7/22 asphyxiated neonates and 1/22 nonaxphyxiated neonate with heart disease (P <0.05). The mostcommon cardiac abnormality found in asphyxiated neonates waspatent ductus arteriosus, followed by atrial septal defect, tricuspid regurgitation, and pulmonary hypertension.Conclusion Cardiac abnormality is significantly found more oftenin asphyxiated than in non-asphyxiated neonates.